WSB1 and IL21R Genetic Variants Are Involved in Th2 Immune Responses to Ascaris lumbricoides - Carneiro, Valdirene Leão; da Silva, Hugo Bernardino Ferreira; Queiroz, Gerson de Almeida; Veiga, Rafael Valente; Oliveira, Pablo Rafael Silveira; Carneiro, Norma Vilany Queiroz; Pires, Anaque de Oliveira; da Silva, Raimon Rios; Sena, Flavia; Belitardo, Emilia; Nascimento, Regina; Silva, Milca; et al. (Frontiers in Immunology, 2021)
Genetic and epigenetic factors are considered to be critical for host-parasite interactions. There are limited data on the role of such factors during human infections with Ascaris lumbricoides. Here, we describe the potential role of genetic factors as determinants of the Th2 immune response to A. lumbricoides in Brazilian children. Stool samples were collected from the children to detect A. lumbricoides by microscopy and peripheral blood leukocytes (PBLs) were cultured in whole blood cultures for detection of cytokines (IL-5, IL-10, and IL-13) in vitro. Levels of anti-A. lumbricoides IgE and IgG4 were measured in plasma. DNA was extracted from PBLs and genotyped using Illumina 2.5 Human Omni Beadchip. Candidate genes associated with A. lumbricoides responses were identified and SNVs in these selected genes associated with the Th2 immune response to A. lumbricoides. Haplotype, gene expression, and epigenetic analyses were done to identify potential associations with Th2 immune responses. GWAS on samples from 1,189 children identified WSB1 as a candidate gene, and IL-21R was selected as a biologically relevant linked gene for further analysis. Variants in WSB1 and IL21R were associated with markers of Th2 immune responses: increased A. lumbricoides-specific IgE and IL-5/IL-13 by PBLs from infected compared to uninfected individuals. In infected children, WSB1 but not IL21R gene expression was suppressed and increased methylation was observed in the WSB1 promoter region. This is the first study to show an association between genetic variants in WSB1 and IL21R and Th2 immune responses during A. lumbricoides infections in children. WSB1/IL21R pathways could provide a potential target for the treatment of Th2-mediated diseases.